Analisis Risiko Kesehatan Pencemaran Timbal (Pb) Pada Kerang Hijau (Perna viridis) di Perairan Cilincing Pesisir DKI Jakarta - Anna Rejeki Simbolon (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Health Risk Assessment of Lead (Pb) Pollution in Green Mussel (Perna viridis) at Cilincing Waters, DKI Jakarta Littoral. Cilincing waters is one of the river estuaries on the coast of DKI Jakarta with increasing industrial and community activities. These activities certainly produce waste that contains heavy metal lead and into the water. Water pollution will affect the health of humans who interact directly or indirectly in these waters. Green mussel (Perna viridis) is one of the dominant benthic biota in Cilincing Waters and becomes one of the food for the people of DKI Jakarta. Green mussels exposed to lead metals at a certain concentration will adversely affect human health. So that required analysis of water pollution to health risks that may occur. This study aims to analyze the health risks of pollution, especially lead metals found in green mussel against humans. The research was conducted in Cilincing Coastal Waters of DKI Jakarta, from September to December 2017 by using survey method to determine the condition of existing environment. Parameters analyzed included Total Suspended Solid (TSS), Pb metal in water, sediment and green mussels. Health risk analysis of lead metal pollution is carried out using the SEDISOIL risk analysis model. This study shows that the concentrations of Pb metal in sediments and green mussels have been above the quality standard so that green mussels from that area are not feasible for consumption by the community. This is evident from the health risk (RQ) noses that have exceeded each sample location